Manufacture and Characterization of Pineapple Leaf Fiber Composite Board With Polypropylene Adhesive - Fatimah Marwa Nasution (Jurnal Matematika Dan Ilmu Pengetahuan Alam LLDikti Wilayah 1 (JUMPA), 2021)
Research has been conducted on the manufacture and characterization of pineapple leaf fiber composites – polypropylene matrix. Samples with comparison of pineapple leaf fiber composition: polypropylene matrix by 0 %: 100%, 5%: 95%, 10%:90%, 15%:85%, 20%;80%, and 25%:75%. The manufacture of SDN-PP composites, i.e. fiber soaked with NaOH 5% for 2 hours and then rinsed with clean water and dried, then weighed. Polypropylene and MAPP are effluxed with xylen solvent using a reflux device over a hot plate with a temperature of 17oC until melted. The polypropylene that has been diflux weighed in mass and pineapple leaf fibers are placed into a mold then pressed with a hot press at a temperature of 150oC for 30 minutes. The purpose of the study was to find out the physical and mechanical properties of pineapple leaf-matrix polypropylene fibers. Density values 0.75 g/cm3 to 0.9 g/cm3, water absorption values 0.54% to 14.38%, strong compressive values 25.09 MPa to 49.58 MPa, and strong values impact 9.74 J/mm2 to 34.18 J/mm2. Pineapple leaf fiber composite – the resulting polypropylene matrix can be categorized as a high-crust fiberboard (HF) and applied as a decorative board in accordance with the fiberboard standards set out in SNI 01-4449-2006.